The land structure of the State of Goiás: mediations and content underlying private land ownership - Silva, Edson Batista da (GEOUSP Espaço e Tempo (Online), 2023)
The historical domination of the land in Brazil has meant the domination of the territory, control of the state, and its public funds. As a living contradiction, fences curtailed the right to land and gave rise to the struggle for land and for agrarian reform. In the meantime, this article presents the contemporary land structure of the state of Goiás and discusses the historical mediations of its constitution. To that end, bibliographical and documentary research were carried out. The results show that the struggle for land and for agrarian reform, responsible for land regularization and expropriation, culminated in 426 settlements with 23,670 families settled. Latifundia hold 62% of the area in hectares and 6.10% of the rural properties in the state of Goiás. On the other hand, minifundia and small properties control 76.23% of the properties and 17.93% of the real state area.